Replacement of maize by different levels of triticale on performances and meat yield characteristics of broiler chickens - Mahbub, ASM; Baqui, MA; Sarker, NR (International Journal of Natural Sciences, 2011)
An experiment was conducted for a period of 5 weeks with 240 day-old cobb-500 broiler chicks and were allocated into six dietary treatments with isocaloric and isonitrogenous containing 2975 Kcal ME/kg DM & 21.70% CP and 3077 Kcal ME/kg DM & 20.34% CP both starter and finisher ration respectively. There were 40 chicks per treatment, each treatment had 4 replication having 10 chicks in each. The dietary treatments were T1 (0% triticale + 100% maize), T2 (20% triticale + 80% maize), T3 (40% triticale + 60% maize), T4 (60% triticale + 40% maize), T5 (80% triticale + 20% maize) and T6 (100% triticale + 0% maize). The broilers of all treatment groups were supplied feeds and water ad libitum throughout the experimental period. There were no significant differences (P>0.05) in feed intake, final body weight, total gain, feed conversion efficiency, survivability% but feed cost per kg live broiler production was differed significantly (P<0.01) among dietary treatments at 35 days of age. Therefore, it is clear that triticale is a good alternative cereal for broiler diet without affecting performance and it may safely replace up to 100% of maize but 40% replacement enhance production performance and edible meat yield of broiler and reducing feed cost (Tk. 2.88/kg) per unit of broiler production. Keywords: Triticale; maize replacement; production performance; meat yield characteristics DOI: http://dx.doi.org/10.3329/ijns.v1i1.8613 International Journal of Natural Sciences (2011), 1(1):25-30